Letter to Jane Tolmach from R.E. - R.E.:::::: (1967)
A letter that suggests modeling an Issues Conference invitation after a colorful Frank Sinatra Gala invitation to attract large attendance and improve finances. Proposed themes such as "Let's Get the Party Moving Again" or "Swinging Again" are recommended, along with eye-catching artwork and possible fundraising events like an Advisory Committee cocktail party. The letter also discusses logistics, including multiple mailings, banquet capacity limits, and coordination with Charlotte and Jane Tolmach and other Women's Division leaders to assist with planning.